Camera to compass: unravelling the impact of travel vlogs on tourist visit intentions - Islam, Md. Tariqul; Kumar, Jeetesh; Yee, Wong Foong; Hussin, Siti Rahayu; Ragavan, Neethiahnanthan Ari (University of Primorska, 2024)
Travel vlogs are considered as video forms of online review, usually generated by tourists and mainly shared on social media platforms. They provide a visual and personal perspective of a destination, inspiring and guiding viewers on where to go and what to do. This study identified the impact of travel vlog videos on tourists’ visit intentions by collecting 231 responses from Bangladeshi residents with a structured, self-administered survey. The findings indicated that tourists perceive travel vlog videos as valuable and trustworthy based on the quality of travel vlog information and vlogger credibility, which subsequently influence the tourists to adopt the vlog information and their visit intention. Theoretically, this study contributes by extending the Information Adoption Model (IAM) with information trust and tourists’ visit intention. Practically, the present study provides several implications for tourism stakeholders, specifically destination marketing organisations (DMOs). Finally, the study concludes by indicating several limitations and recommendations for future research.